College as a Risk Factor for Victimization: Results from the National Crime Victimization Survey - Reyns, Bradford W. (Victims & offenders, 2022)
A substantial body of victimization research has focused on college students as a unique population of crime victims. These studies generally suggest that college students have high rates of victimization for specific crimes. However, it is unclear to what extent college student status confers an increased victimization risk for students, relative to other risk factors, such as age and sex. This study utilizes a pooled sample of U.S. residents from the National Crime Victimization Survey (2017–2019) to examine three types of criminal victimization against persons age 18–24. College enrollment, and living on campus, are assessed as potential determinants of victimization risk. The results suggest complex relationships between these college variables and risks for criminal victimization, with college enrollment and campus living increasing or decreasing the likelihood of victimization depending on the crime.